Evolution Now - Berridge, Mike (New Zealand Science Review, 2018)
​There is no mistaking the engaging and unconventional conversational writing style used by David Penny in his book Evolution Now that traces the development of current evolutionary theories, and provokes thought on unresolved questions. Through undergraduate studies at the University of Canterbury where he was exposed to the teachings of Karl Popper, Penny embraces the Popperian school of science philosophy, in which the words ‘believe’ and ‘prove’ are anathema to the scientific method and progress occurs through falsification involving exhaustive testing of hypotheses. Too often today, scientists seek to prove their ideas right rather than testing strong hypotheses, and multiple weak hypotheses are frequently formulated around highly specific objectives, sometimes bordering on anti-science. To a large extent, this is due to our failure to understand the basis of scientific methodology, fuelled by a science funding system where preliminary results, often near publication, are rewarded, and novel game-changing hypotheses are relegated to the bottom of the pile. This is perhaps a lesser problem with Mardsen funding, and with Health Research Council Explorer grants where qualifying transformative applications are subjected to a lottery process.